2023
DOI: 10.1007/s10142-022-00955-4
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA34977 promotes the proliferation, migration, and invasion and inhibits the apoptosis of canine mammary tumors by regulating the expression of miR-8881/ELAVL4

Abstract: Long-stranded noncoding RNAs (lncRNAs) play different roles in various diseases. lncRNA34977 has been shown to play a relevant role the development of canine mammary tumors (CMTs). However, the mechanism of lncRNA34977 in canine mammary tumors has not been fully investigated. The aim of this study was to investigate the effects of lncRNA34977 on the proliferation, migration, invasion, and apoptosis of canine mammary tumor (CMT) cells through the regulation of miR-8881/ELAVL4 expression. The apoptosis was detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…These results indicate that lncRNA can function as a promoter or an inhibitor of tumor progressions. Another study has shown that lncRNA 34977 promotes the development of canine mammary tumor cells and suppresses apoptosis by directly targeting miR-8881/ELAVL4 [26]. Chemotherapy resistance is a significant factor contributing to the failure of canine mammary tumor treatment.…”
Section: The Molecular Function and Clinical Use Of Lncrna As Canine ...mentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that lncRNA can function as a promoter or an inhibitor of tumor progressions. Another study has shown that lncRNA 34977 promotes the development of canine mammary tumor cells and suppresses apoptosis by directly targeting miR-8881/ELAVL4 [26]. Chemotherapy resistance is a significant factor contributing to the failure of canine mammary tumor treatment.…”
Section: The Molecular Function and Clinical Use Of Lncrna As Canine ...mentioning
confidence: 99%
“…Mammary tumor lncRNA 40589 inhibits cell proliferation, migration, and invasion [24] lncRNA 34977 promotes the development of tumor cells and suppresses apoptosis [24] lncRNA 42060 inhibiting tumor cell progression [26] Melanomar lncRNA SOX21-AS regulatory elements in the cell cycle and carbohydrate metabolism [33] lncRNA ZEB2-AS regulatory elements in the cell cycle and carbohydrate metabolism [33] lncRNA CASC15 regulatory elements in the cell cycle and carbohydrate metabolism [33] lncRNAs ENSCAFT00000069599.1 correlation with the patient's ROC [34] lncRNAs ENSCAFT00000090032.1 NA [34] Lymphomar A group of lncRNAs a non-negligible fraction of human DLBCL [42] A group of lncRNAs differentiates B-cell lymphoma subtypes and indicates mortality rates [43] Soft tissue sarcoma lncRNA TERRA regulates the cell growth [44] Osteosarcoma lncRNA MALAT1 regulates the cell growth [45] MDCK tumorigenicity lncRNA MSTRG.1056.2 contributes to tumorigenesis [49] NA: Has not been tested.…”
Section: Cancer Types Lncrna Function Referencementioning
confidence: 99%
“… 8 LncRNA34977 is a lncRNA that is highly expressed in canine mammary tumors. It can promote progression of canine mammary tumors through regulating the expression of miR-8881/ELAVL4, 9 LncRNA DANCR functions as a miR-33b sponge to positively regulate proliferation and metastasis in pancreatic cancer. 10 Suman Ghosal et al 11 identified a large number of non-coding transcripts as immune response-related genes through the ceRNA network.…”
Section: Introductionmentioning
confidence: 99%